The molecular mechanism of cardiac injury in SARS-CoV-2 infection: Focus on mitochondrial dysfunction - Yang Shen; Min Chen; Wei Gu; Jianwei Wan; Zhihui Cheng; Kan Shen; Wen Zhang; Jinming He; Yunfeng Wang; Xingqi Deng (Elsevier, 2023)
Background: Coronavirus disease 2019(COVID-19) caused a large number of infections worldwide. Although some patients recovered from the disease, some of the other problems that accompanied it, such as cardiac injury, could affect the patient's subsequent quality of life and prognosis. Objectives: To clarify the molecular mechanism of cardiac injury in SARS-CoV-2 Infection. Methods: The RNA-Seq dataset (GSE184715) comparing expression proﬁling of Mock human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) and SARS-CoV-2-infected hiPSC-CMs was downloaded from Gene Expression Omnibus (GEO). Differentially expressed genes(DEGs) were performed by the R software. Degs were analyzed by enrichment analysis to clarify the affected pathways. Hub genes were screened out by a PPI network constructed from Degs. Finally, Connectivity Map was used to screen for the treatment of COVID-19 induced cardiac injury. Results: 2705 differentially expressed genes were identified. Enrichment analysis confirmed that mitochondrial dysfunction was caused by SARS-CoV-2, meanwhile, cardiac muscle contraction was suppressed and NF-κB was activated. Based on the PPI network, 15 hub genes were identified. These 15 down-regulated hub genes were mainly involved in the reduced activity of complexes in the mitochondrial respiratory chain associated with mitochondrial dysfunction. Moreover, 5 candidate drugs were identified to treat cardiac injury. Conclusion: In conclusion, SARS-CoV-2 infection of cardiomyocytes causes mitochondrial dysfunction, including reduced mitochondrial respiratory chain complex activity and decreased ATP synthesis, leading to cardiomyocyte apoptosis, while the activated NF-κB also induced cytokine storms, ultimately resulting in cardiac injury.